ChemInform Abstract: Oxidations of Alkenes with Hypervalent Iodine Reagents: An Alternative Ozonolysis of Phenyl Substituted Alkenes and Allylic Oxidation of Unsubstituted Cyclic Alkenes. Issue 37 (16th September 2014) - Atmaca, Ufuk; Usanmaz, Hande K.; Celik, Murat
Abstract All presented reactions are performed with iodosylbenzene as well as iodylbenzene with the latter giving slightly higher yields of the desired products.